An Obstacles in Implementing The Regulation of The Minister of ATR/BPN Number 11 and 14 of 2021 in The Preparation of The Kalibawang Urban RDTR - Adriani, Rizqi Amalia; Setyasih, Iya`; Sandy, Aisyah Trees (Universitas Negeri Semarang, 2024)
The Kalibawang Urban RDTR for 2022-2042 will see adjustment to the Minister of ATR/BPN Regulation No. 11 and No. 14 of 2021, aims to analyze obstacles to implementing ATR/BPN Ministerial Regulation No. 11 and No. 14 of 2021 in the preparation for the Kalibawang Urban RDTR. This research uses descriptive methods with qualitative research with data collection is carried out by observation dan documentation, and data analysis are Miles and Huberman (1984) consisting of data reduction, data display, and conclusion. Data collection originates from RDTR database of Kalibawang Urban RDTR material documents in the form of technical material, factual analysis material, policy study drafts, and the 2018 Kalibawang Urban RDTR draft. Data reduction is related to analyzing the obstacles in implementing the ATR/BPN Ministerial Regulation Number 11 and ATR/BPN Ministerial Number 14 of 2021 compare material: RTRW Kulon Progo Regency for 2012-2032 and Draft RDTR for Kalibawang City for 2022-2042, material for RTRW for Bontang Regency for 2019-2039 and RDTR for Bontang City for 2016-2036, as well as material on the East Kutai Regency RTRW 2015-2035 and the Sangatta Urban Area RDTR 2022-2042. Display data related to RDTR database material in a geodatabase via a Geographic Information System (ArcGIS), planning maps, and technical material documents. Concluding the results of the analysis results in obstacles to ATR/BPN Ministerial Regulation Number 11 of 2021 concerning the stages of preparing the RDTR: difficulty finding RDTR data and information, the process of obtaining image data takes time, adjusting the standard classification code for Indonesia fields in 2020 to four or five digits, checking special provisions, classification of spatial structure plan content and spatial patterns, and adjusting RDTR loads with Kulon Progo RTRW and regulations. Obstacles in implementing ATR/BPN Ministerial Regulation No. 14 of 2021 regarding the preparation of the database and presentation of RDTR maps: re-delineation of the RDTR map by the Decree of the Regent of Kulon Progo Number 190 of 2021, adjusting the timing of RDTR, image recording data, lack of RDTR data and information for various sectors, and checking spatial pattern maps compares to other images.